Social support and technophobia in older patients with coronary heart disease: The mediating roles of eHealth literacy and healthcare technology self-efficacy - Jianchun Zhao; Danqing Hu; Haowei Du; Haichao Wang; Xiaomin Tu; Aimin Wang (PLoS ONE, 2025)
Objectives The purpose of this study was to explore the relationship between social support, eHealth literacy, healthcare technology self-efficacy, and technophobia. It also analyzed the mediating effect of eHealth literacy and healthcare technology self-efficacy between social support and technophobia. Methods Older patients with coronary heart diseases (n = 396) from four communities in Qingdao were interviewed using the Technophobia Scale, Social Support Rating Scale, eHealth Literacy Scale and Healthcare Technology Self-Efficacy Scale. Data were analyzed using common method deviation test, Pearson’s bivariate correlation analysis, and mediation analysis using the PROCESS macro. Results Social support was significantly positively correlated with eHealth literacy (r = 0.614, p < 0.01) and healthcare technology self-efficacy (r = 0.635, p < 0.01), and significantly negatively correlated with technophobia (r = −0.578, p < 0.01). eHealth literacy was significantly positively correlated with healthcare technology self-efficacy (r = 0.822, p < 0.01), and significantly negatively correlated with technophobia (r = −0.651, p < 0.01). Healthcare technology self-efficacy was significantly negatively correlated with technophobia (r = −0.700, p < 0.01). Social support had a total indirect effect on technophobia of −0.410, with eHealth literacy and healthcare technology self-efficacy mediating 24.9% and 30.2% of this effect respectively, and the chain mediating effect accounting for 44.9%. Conclusions Our findings provide a theoretical reference for nursing to develop appropriate interventions to alleviate technophobia among older patients with CHD.